Gender Gaps and Economic Development: The Impact of Inequality in Nigeria - Okutimiren, Adeteji O.; Ubani, Chidi U.; Ogunjobi, Olalekan F.; Omitogun, Olawunmi (NIU Journal of Social Sciences; Vol 10 No 4 (2024): NIU Journal of Social Sciences, Vol. 10 No. 4 December 2024, 2024)
Economic development relies heavily on human capital, yet persistent gender inequalities, where women are significantly underrepresented in education and various sectors, present a major barrier to progress, limiting both women’s potential and overall economic productivity despite global efforts to address these disparities. Therefore, this study aims to assess the gender inequalities influences economic development. The study utilizes time-series data for Nigeria spanning from 1986 to 2022, employing the autoregressive distributed lag-error correction model (ARDL-ECM) methodology developed by Pesaran et al. (2001) for the analysis. The results suggest that while there is some progress in female education, existing policies aimed at improving gender parity may not be effectively translating into economic development. The study recommends prioritizing policies that ensure equal opportunities and working conditions, and eliminating gender discrimination to increase women’s contributions to economic development. Keywords: ARDL, Gender Inequality, Economic Development, Human Capital, Nigeria